The challenges and opportunities of COVID-19 for Islamic microfinance institutions in Bangladesh - Uddin, Md Nazim; Haque, A K M Ahasanul; Anis, Zohurul (Springer, 2024)
This study focuses on the Urban Poor Development Scheme (UPDS) and the Rural Development Scheme (RDS), both of which are types of Islamic Microfinance Institutions. It examines the effects of the COVID-19 pandemic on these two categories of Islamic Microfinance Institutions (IsMFIs). The significant decline in economic activity during the pandemic has significantly impacted the lives of several people, especially those who are debtors of multinational Islamic Microfinance Institutions (IsMFIs). A more robust understanding of the need for financial inclusion and increased demand for digital financial services are two instances of the potential that Bangladeshi IsMFIs have identified their challenges. The significance of this research lies in the pivotal role that IsMFIs assume in alleviating poverty at the national level, namely among marginalized populations. This study fills the knowledge gap about the opportunities and challenges that COVID-19 poses for IsMFIs operating in Bangladesh. The principle behind this methodology is library research, which entails gathering and assessing data from various sources. Yearly reports from UPDS, RDS, and the Bangladesh Bureau of Statistics supplement data gathering. The study process was underpinned by the use of robust quantitative research methodologies. Strategies for expanding foreign financial institutions in Bangladesh following the COVID-19 pandemic are formulated based on the study results, highlighting the potential for significant growth and expansion in this sector. Due to the COVID-19 pandemic's impact on the microfinance sector, this study examines the current scholarly discourse on the obstacles and prospects that IsMFIs in Bangladesh encounter. Furthermore, it will furnish astute insights concerning these obstacles and prospects. This study's findings provide practical guidance for policymakers and other stakeholders in advocating for IsMFIs, thereby mitigating the disease's impact on Bangladesh's impoverished population.